Konsep Forgiveness di Minangkabau - Novitasari, Novitasari; Adri, Zakwan (JURNAL PSIKOLOGI INSIGHT, 2022)
Abstract Forgiveness is a psychological construct occurring often in daily life when people have personal interaction each other. The cultural stereotype of forgiveness among ethnics in Indonesia is unique to discuss. This study is aimed at identifying the concept of forgiveness in people at Minangkabau culture. This study used qualitative method with indigenous psychology approach.  This study ask participants four open-ended questions and 2 close-ended questions though google form application. Data were collected from 170 participants of from Minangkabau culture living both in West Sumatra Province and other towns outside the province. Data were analyzed with thematic analysis and used tabulation to the data achieved and researcher used coding and categorization toward the data. Results suggest that participants are difficult to forget the mistakes of those who did something hurt them, but didn’t avoid them, expected punishment for people who had hurt them, and do good towards people who hurt them. It can be concluded that there are four concepts of forgiveness in this sample of ethnic: challenge, hope, revenge, and good deeds.Keywords: forgiveness, indigenous, minangkabau, stereotypeAbstrak Forgiveness merupakan konstruk psikologi yang sering terjadi dalam kehidupan sehari-hari dalam interaksi interpersonal. Stereotip dalam konsep  forgiveness berdasarkan suku dan budaya di Indonesia memiliki pola yang unik. Penelitian ini bertujuan untuk mengidentifikasi konsep forgiveness dalam masyarakat etnis Minangkabau. Peneliti menggunakan metode kualitatif dengan pendekatan psikologi indigenous. Penelitian ini menggunakan empat pertanyaan terbuka dan dua pertanyaan tertutup melalui aplikasi google form. Studi mengumpulkan data dari 170 orang bersuku Minang yang berada di Sumatera Barat dan luar Sumatera Barat. Data diolah menggunakan analisis tematik dan menggunakan tabulasi terhadap data dimana peneliti melakukan proses koding dan kategorisasi. Hasil penelitian menunjukkan bahwa partisipan sulit melupakan kesalahan orang yang telah menyakitinya, tetapi tidak menghindari mereka, mengharapkan adanya hukuman bagi orang yang telah menyakitinya, serta berbuat baik terhadap orang yang telah menyakitinya. Hasil ini menunjukkan bahwa terdapat empat konsep forgiveness dalam masyarakat etnis Minangkabau yaitu tantangan, harapan, balas dendam dan kebaikan.  Kata kunci: forgiveness, indigenous, minang, stereotip